Underwater Acoustic Imaging of the Sea - Grażyna GRELOWSKA; Eugeniusz KOZACZKA (Archives of Acoustics)
Acoustic waves are a carrier of information mainly in environments where the use of other types of waves, for example electromagnetic waves, is limited. The term acoustical imaging is widely used in the ultrasonic engineering to imaging areas in which the acoustic waves propagate. In particular, ultrasound is widely used in the observation of human organs – ultrasonography (Nowicki, 2010).